Penerapan Pembelajaran Tata Cara Haji Menggunakan Augmented Reality - Agustina, Dian Resha; Aprilinda, Yuthsi; Susanty, Wiwin; Suharmoko, Suharmoko (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2024)
The majority of the population in Indonesia is of Islamic faith. Hajj is a form of worship in Islam with its own rules and regulations, consisting of conditions and pillars that must be performed perfectly. However, in reality, many Indonesian pilgrims still don't fully understand the procedures of Hajj. Therefore, one solution to overcome the limitations of the required media for learning Hajj rituals is by combining the Android platform and Augmented Reality technology. Augmented Reality (AR) involves the virtualization of digital information or computer-generated content such as audio, video, images, and touch, making it seem as though they exist in the real-world environment. Augmented reality finds applications in various fields, particularly in education, such as the Hajj pilgrimage rituals. By merging real and virtual objects, 3D objects are displayed using markers. These markers, detected by Android smartphone cameras, display their corresponding 3D objects during the Hajj rituals. This is the foundation for researchers to implement a learning method for Hajj rituals using Android-based smartphones with Augmented Reality technology. Using smartphones makes it more convenient and flexible, and by incorporating Augmented Reality technology, it adds an interesting and enjoyable element to the learning process. The objective of this research is to implement augmented reality technology, particularly for Hajj pilgrims, in order to assist them in comprehending the methods of performing the Hajj pilgrimage in an engaging and easily understandable manner. The application allows users to view animated video models and textual explanations of the Hajj rituals.